Impact of frailty on survival and readmission in patients with gastric cancer undergoing gastrectomy: A meta-analysis - Wang, Xiaoyan; Sun, Yimeng; Wang, Pei; Jie, Yu; Liu, Guodong; Gong, Dandan; Fan, Yu (Frontiers in Oncology, 2022)
Background: Frailty as a common geriatric syndrome can affect the clinical outcomes in patients with gastric cancer. However, the impact of frailty on survival and readmission patients with gastric cancer has not been well-characterised. Objectives: To investigate the impact of frailty on survival and readmission in patients with gastric cancer undergoing gastrectomy by conducting a meta-analysis. Methods: Eligible studies were identified by searching the PubMed, Web of Science, Cochrane Library, and Embase databases until September 2, 2022. Observational studies that evaluated the value of frailty in predicting adverse outcomes in gastric cancer patients undergoing gastrectomy were included. The outcomes of interest were overall survival, disease-specific survival (death from gastric cancer), and readmission. Adjusted hazard ratios (HR) with 95% confidence intervals (CI) were pooled to calculate the association of frailty with adverse outcomes. Results: Eight studies reported on 9 articles with 2792 patients with gastric cancer were included. A fixed effect meta-analysis indicated that frailty was associated with a reduced in-hospital overall survival (HR 2.08; 95% CI 1.46–2.95), long-term overall survival (HR 1.84; 95% CI 1.37–2.47), and disease-specific survival (HR 1.94; 95% CI 1.34–2.83). In addition, frailty was associated with increased risk of readmission within 1-year (HR 3.63; 95% CI 1.87–7.06). Conclusions: Frailty was associated with a reduced overall survival and disease-specific survival and an increased risk of readmission in patients with gastric cancer undergoing gastrectomy. Frail status may play an important role in the risk stratification of gastric cancer after gastrectomy.